Synthesis and Quantum Chemical Calculations of 4-(2-Fluorophenyl)- 1-(2-oxoindolin-3-ylidene)thiosemicarbazone and its Zinc(II) Complex - Kandemirli, F.; Akkaya, Y.; Vurdu, C. D. (Asian Journal of Chemistry, 2013)
In this study, wavenumbers, IR intensities and molecular parameters of 4-(2-fluorophenyl)-1-(2-oxoindolin-3-ylidene)thiosemicarbazone (I2FPTH(2)) and its zinc(II) complex have been studied theoretically by using the ab initio Hartree-Fock (HF) method with the 3-21G, 3-21G*, 6-31G(d,p), 6-311G (d,p), 6- 311++G (d, p) and 6-311++G (2d,2p) basis sets. In addition to theoretical study, they have been prepared for characterization of structure by means of elemental analyses which are FT-IR, electronic and H-1 NMR Zn(II) complex spectra. Moreover, according to the results of Fukui functions values of I2FPTH2, calculated with B3LYP/6-31G(d,p) and B3LYP/6-311G(d,p), the contribution of sulphur to the HOMO is found predominant 47.69 and 49.16 %, respectively while the contribution of nitrogen to the LUMO is also found dominant as 24.82 and 24.21 %, respectively. The theoretical results of wavelengths, H-1 and C-13 NMR for wavenumbers are sensibly consistent with the results of experimental study.
Keywords: H-1 NMR; C-13 NMR; FT-IR spectra; Thiosemicarbazone; DFT